Study The Variations In Al-Hawizeh Marsh Area Using Maps And Satellite Images - Rasheed, Muaed; Sultan, Maitham (Iraqi Journal of Science, 2024)
The study area is located in the alluvial plain of Iraq, and specifically in thelower floodplain of the Tigris River, and a low naturally extends to a wide area andat a shallow depth and works a source of the floods when they occur, and it receivesexcess water for various uses. We are using ancient and modern maps with largescales to see the shape and space boundaries Al-Hawizeh Marsh, was the work mockmaps of the area through a series of satellite images of different dates and with thehelp of remote sensing techniques.From the comparing to Al-Hawizeh Marsh area and make an exact time map of themarsh shows that the marsh has passed through several stages. Through this researchthat we shows the variance in the change recharges rivers rates that feeding of theMarsh at the months, seasons and years due to the climate changes of this region,